Effect of posture on pulmonary function in the third trimester of pregnancy of primigravid, nulliparous and multiparous women in Benin City - Omorogiuwa A; Osazee K (Ibom Medical Journal, 2018)
BACKGROUND: the advancing gravid uterus poses a limited lying down posture options in the third trimester. The supine position has been documented to have deleterious cardiovascular effect. This study is aimed at measuring pulmonary function of pregnant women in the third trimester of pregnancy with some lying down positions viz a viz parity. MATERIALS AND METHOD: It was a cross sectional study carried out at St Philomena's Catholic Hospital. A total of 150 third trimester pregnant subjects in 5 groups of parities with 30 in each group and in different lying down were studied. Spirometric measurements of forced vital capacity (FVC) and forced expiratory volume in one second (FEV1) were performed in sitting position which served as the control, and the test positions were supine, left lateral and right lateral. RESULT: FVC and FEV1 values of all subjects in all positions studied were significantly lower than the sitting position. However, the FVC and FEV1 of subjects in the lateral positions were significantly higher (p < 0.05) than the supine position across parities. There was no significant difference (p > 0.05) between the left lateral position and the right lateral positions. Furthermore there was an increase in FVC and FEV1 of subjects as the parity increases across all lying down position. CONCLUSION: Supine position in the third trimester of pregnancy has a negative effect on pulmonary function and should be discouraged; parity however has a cumulative positive effect on pulmonary function across the postures studied.